Environmental Management Proposal to Increase Productivity in a Municipal Camal Through a Plant Redistribution Design - Alcalá Adrianzén, Miguel Enrique; Salazar Nuñez, Rosa Lucia; Castillo Quezada, Diego Alonso (LACCEI, 2024)
The present investigation focused on carrying out an analysis of the environmental impact produced by a municipal canal in the province of Trujillo, department of La Libertad, based on this, through a risk analysis, the activities that generated a greater risk were defined, and then evaluated through The Leopold matrix is the most affected environmental factor resulting from the production process of a municipal slaughterhouse. As a result, soil and water were defined as the most affected factors, so that later, by applying a plant layout redesign based on the Systematic Layout Plannig tool, the areas can be approximated according to degrees of importance, and the In turn, increase productivity by taking advantage of space and reducing transportation times. Finally, an increase in productivity by 56.87% was obtained and at the same time a reduction in solid waste by moving the waste generating areas closer to the waste area.